answersLogoWhite

0

(4 + 2x) - (-2x + 1) = 13 + 6

4 + 2x + 2x -1 = 19

4x +3 = 19

4x = 19 - 3

4x = 16

therefore x = 16/4

x = 4

User Avatar

Wiki User

14y ago

Still curious? Ask our experts.

Chat with our AI personalities

FranFran
I've made my fair share of mistakes, and if I can help you avoid a few, I'd sure like to try.
Chat with Fran
LaoLao
The path is yours to walk; I am only here to hold up a mirror.
Chat with Lao
ViviVivi
Your ride-or-die bestie who's seen you through every high and low.
Chat with Vivi

Add your answer:

Earn +20 pts
Q: 4 plus 2x- -2x plus 1 equals 13 plus 6?
Write your answer...
Submit
Still have questions?
magnify glass
imp